1974
DOI: 10.1149/1.2401800
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Vapor Deposited Tungsten for Semiconductor Metallizations

Abstract: The properties of CVD tungsten films, produced by the hydrogen reduction of WF6 or WCl6, have been investigated to determine the suitability of the films for use as silicon integrated circuit metallization.s. Both low pressure and atmospheric pressure flow system have been investigated.The tur~gsten films show excellent adhesion to silicon substrates, have resistivities between 6 and 15 #ohm-cm depending on thickness, and are easily etched into submicron patterns. In addition, data on the contact resistance to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

1974
1974
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(7 citation statements)
references
References 2 publications
2
5
0
Order By: Relevance
“…The weight of this self-limiting W layer resulting from the WF 6 reduction in the Ar atmosphere corresponds to a film thickness of 26 nm 16 in excellent agreement with measurements performed by Melliar-Smith et al 18 and Yu and Eldridge. In the absence of H 2 , only reactions ͑1͒ and ͑2͒ may occur, and the weight of the W seed layer was found 0.0040Ϯ0.0003 g, which is within the two-sigma uncertainties of the values obtained from both the HF and H 2 data.…”
Section: E Nucleation On the Si Surfacesupporting
confidence: 88%
“…The weight of this self-limiting W layer resulting from the WF 6 reduction in the Ar atmosphere corresponds to a film thickness of 26 nm 16 in excellent agreement with measurements performed by Melliar-Smith et al 18 and Yu and Eldridge. In the absence of H 2 , only reactions ͑1͒ and ͑2͒ may occur, and the weight of the W seed layer was found 0.0040Ϯ0.0003 g, which is within the two-sigma uncertainties of the values obtained from both the HF and H 2 data.…”
Section: E Nucleation On the Si Surfacesupporting
confidence: 88%
“…The sheet resistance was measured with a four-point probe and was uniform over the sample within better than 5% for all except the very thinnest films. The resistivity was 13.9 ~12-cm for films about 162 nm thick and decreased to 10.5 ~l-l-cm for films about 430 nm thick, in reasonable agreement with the resistivities reported in the literature (6,7,8). The actual resistivity may be less than that indicated, since surface roughness may increase the apparent film thickness measured with a profilometer on a step etched through the tungsten.…”
Section: Film Depositionsupporting
confidence: 87%
“…(*Total) = (*) + (WF.~*) (*Total) = constant (*WF~) = constant, because it is the MASI Therefore (*), the empty site concentration is also a constant. When invoking (15), the rate equation becomes r = k3(WFs*)Kg'/~H2'/2(*) [16] r = k"(H2) 1/2 [17] where k" = k3(WF.~*)(*)K91/2 A similar rate equation would result from the assumption that any of reactions [2a] through [7a] could be rate limiting. The resulting equations are all zero order in tungsten hexafluoride and one-half order in hydrogen.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors report an activation energy of.67,000-69,000 J mol-' (2,9,11,14,15). Most authors also observed the reduction reaction to be zero order with respect to tungsten hexafluoride and one-half order with respect to hydrogen (2,11,14,15,16). All of the authors reporting a mechanism assumed the rate limiting step to be hydrogen dissociation or HF desorption without rigorously evaluating those mechanisms.…”
mentioning
confidence: 99%